The crowning glory of Calla Lily Ponder [compact disc, unabridged] - Wells, Rebecca, 1952- (Harper Audio, 2009)
In the small river town of La Luna, Calla enjoys a blissful childhood. Her mother, a woman of rapture and love, teaches Calla the art of healing through the humble womanly art of "fixing hair." Calla further learns that this same touch of hands on the human body can quiet her own soul. It is also on the banks of the La Luna River that Calla encounters first love, with a boy named Tuck. But when Tuck leaves Calla with a broken heart, she transforms hurt into inspiration and heads for the wild and colorful city of New Orleans to study at L'Académie de Beauté de Crescent. There she comes to understand fully the power of her "healing hands" to change lives and soothe pain, including her own.